“Tinkers” in Verse: The Dublin Gate Theatre’s Production of Donagh MacDonagh’s God’s Gentry (1951) - Lanters, José (FOCUS: Papers in English Literary and Cultural Studies, 2022)
In his ballad opera God’s Gentry, produced in 1951 at the Dublin Gate Theatre under the direction of Hilton Edwards, Donagh MacDonagh set out to satirize totalitarian regimes and the welfare state by making the “class” of the tinkers the rulers of Ireland for a year, led by Marks (“Marx”) Mongan and aided by the old Irish god Balor of the Evil Eye. Written in verse and interspersed with popular folk tunes to which MacDonagh wrote new lyrics, the play imagines the tinkers’ outlook on life as the antithesis of capitalism, law and order, and Christian family values. Nora, the village shopkeeper’s daughter, is seduced by the free and merry ways of Marks and his people, but when the nation is declared bankrupt and the pagan, socialist “tinker’s republic” collapses, her jilting of Marks and her return to settled life signal a more general reversal of the nation to bourgeois values. This essay considers the way in which Travelling people are represented in the text and on the stage both as metaphorical stand-ins for politicians governing Ireland and nations beyond its borders and as an actual Irish minority perceived as an unregulated and transgressive entity—a “nation within a nation”—by the settled population. The article also considers how the life of the Travellers was imagined aesthetically in what MacDonagh referred to as the “grand” settings and costumes designed for the Gate production by Micheál Mac Liammóir, who also played the part of Marks.